(3, 4-Dihydroxyphenyl)(2, 3, 4-trihydroxyphenyl)methanone and its derivatives as carbonic anhydrase isoenzymes inhibitors. (April 2013) - Nar, Meryem; Çetinkaya, Yasin; Gülçin, İlhami and Menzek, Abdullah
<x xml:space="preserve">Abstract</x> In this study, we have synthesised (3, 4-dihydroxyphenyl)(2, 3, 4-trihydroxyphenyl)methanone and a series of its derivatives (5, 13–16) and tested the ability of these compounds to inhibit two metalloenzyme human carbonic anhydrase (hCA, EC 4.2.1.1) isozymes, hCA I and hCA II. The synthesised compounds showed inhibitory effect on hCA I and hCA II isozymes. The results showed that synthesised compounds (5, 13–16) demonstrated the best inhibition activity against hCA I (IC50: 3.22–54.28 μM) and hCA II (IC50: 18.52–142.01 μM). The compound 14 showed the highest inhibiton effect against hCA I (IC50: 3.22 μM; Ki: 1.19 ± 1.4 μM). On the other hand, the compound 13 showed the highest inhibiton effect against hCA II (IC50: 18.52 μM; Ki: 3.25 ± 1.13 μM).